TOOLS FOR ATTRACTING CITIZENS TO THE ENTERPRISES OF THE FAR EAST - E. Kolesnichenko; D. Zvereva (Вестник Северо-Кавказского федерального университета, 2022)
The article presents the goal-to develop recommendations for the implementation of measures to attract and employ citizens in the enterprises of the Far East. The authors analyze the economic potential of the region, present statistical data on the population in general and the working-age population in particular, and describe changes in the population structure in recent years. Separately, the state employment policy and specific measures to correct the difficult situation in the Far East are considered. The study identified the main causes of difficulties in the employment sector in the region, on the basis of which recommenda tions were proposed for the implementation of measures to attract and employ citizens in enterprises.